2008
DOI: 10.1002/ca.20732
|View full text |Cite
|
Sign up to set email alerts
|

Student views on the introduction of anatomy teaching packages into clinical attachments

Abstract: Following the implementation of the GMC document Tomorrow's Doctors in 1993 the amount of time dedicated to anatomy in undergraduate curricula has been reduced. This has resulted in considerable disquiet among physicians and surgeons with regard to the anatomical knowledge of newly qualified doctors, and also amongst students. This study aimed to assess the perceived student need for anatomical teaching packages to support clinical attachments in the later years of the undergraduate medical curriculum. The vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Anatomy should be taught throughout the curriculum, not just in years 1 and 2, as supported by others (Evans and Watt, 2005; Stringer and Nicholson, 2006; Dawson et al, 2009; Fitzgerald et al, 2009).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Anatomy should be taught throughout the curriculum, not just in years 1 and 2, as supported by others (Evans and Watt, 2005; Stringer and Nicholson, 2006; Dawson et al, 2009; Fitzgerald et al, 2009).…”
Section: Resultsmentioning
confidence: 85%
“…At undergraduate level: Assessment needs to promote relevant learning, e.g., knowledge and application. Students need to be supported in the process of learning anatomy, e.g., provided with information about how to learn anatomy. Anatomy teaching from day 1 needs to highlight the clinical relevance. This should involve integrally the use of surface anatomy and radiology. Anatomy should be taught throughout the curriculum, not just in years 1 and 2, as supported by others (Evans and Watt, 2005; Stringer and Nicholson, 2006; Dawson et al, 2009; Fitzgerald et al, 2009). Anatomy teaching should involve the use of human cadaveric material.At postgraduate level: Revisiting anatomy and refresher courses should be available to all postgraduates.…”
Section: Resultsmentioning
confidence: 93%
“…This provides a strong argument that anatomy teaching should continue in parallel with clinical teaching, with formal teaching interspersed with appropriate clinical placements and at appropriate times (Abu-Hijleh et al, 2005). Vertical integration of anatomy in the medical curriculum would provide increased linking of clinically correlated anatomy to clinical practice, while reinforcing basic anatomical knowledge (AbuHijleh et al, 2005;Evans and Watt, 2005;Dawson et al, 2009). Furthermore, such teaching would prevent overburdening in the first two years as the learning needs of medical students expand.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported the importance of clinically focused vertical integration of anatomical teaching, across all years of undergraduate training, which would ensure medical students are regularly exposed to anatomy throughout their training (Bergman et al, 2008;Dawson et al, 2009). Recent surveys have reflected this view by medical students and doctors, as many feel that they forget a lot of the information through the years and need some revision (Mitchell and Batty, 2009;Ahmed et al, 2010;Smith and Mathias, 2011).…”
Section: Letter To the Editormentioning
confidence: 99%